International Business Communication Management in Cultural Context - Redhiansyah Indra Pramana; Harliantara, Harliantara; Nurannafi Farni Syam Maella (Gudang Jurnal Multidisiplin Ilmu, 2025)
This study explores international communication management in the Department of Investment and One-Stop Integrated Services (DPMPTSP) of East Java in the context of cultural differences. The main findings indicate that DPMPTSP operates in an environment with cultural dimensions such as low power distance, individualism, masculinity, low uncertainty avoidance, and long-term orientation. This affects the way the institution communicates and manages its international relations. The study found that adapting communication that is sensitive to cultural differences, including values, attitudes, and etiquette, is essential to improving operational effectiveness and efficiency. The novelty of this study lies in the in-depth understanding of the application of Hofstede's cultural theory in the context of international communication management in the public sector, as well as practical recommendations to overcome cultural challenges in international interactions.